The Condition and Context of Mosque Organizations in Phuket Province: Developing Muslim Communities Towards Morality and Ethics - อิสลาม ศอดรีย์; Sidae, Waeyosof (Al-HIKMAH Journal, 2024)
This research is qualitative research. The objective is to study the conditions and context of the Phuket Provincial Mosque Organization that develops the Muslim community towards morality and ethics. and study guidelines for Muslim community development by mosque organizations in Phuket province Collection of data from documents related to various contents Be a part and use the information obtained to create questions to conduct group interviews. along with specifying sub-topics Analysis and presentation of analysis results in the form of descriptive reports analyzed according to the specified objectives. The results of the study found that Muslim social context found in Phuket province There are factors that affect the background of Islam and the creation of a moral Muslim community in this province as follows: 1) Muslim population: Phuket province has a Muslim community with Muslim people living. which come from various nationalities and nationalities This is because Phuket is a tourist destination. This creates a gathering and pride in the hospitality of the people in the area. and has a beautiful Thai culture As a result, the working organization has the potential to develop more morality. 2) Important places: This is because Phuket has 5-star hotel accommodations in many hotels. The mosque is also considered a place to visit in terms of moral development. and is considered an important place for visitors, such as mosques, which are places for ibadah (prayers) and other religious activities. 3) Social Context Local social conditions, culture, and cultural diversity found in Phuket affect the local Islamic religion. 4 ) Education and understanding of religion Education about Islam and understanding the diversity of Islam will play an important role in creating understanding and common precepts in the local area. 5) Adaptation: Adaptation of Islam to local conditions. And blending with the local culture is important to create a balanced background.